Effect of diurnal variation on body composition under consideration of selected chronobiological marker systems - Dittmar, Manuela; Raschka, Christoph; Koch, Horst J. (Anthropological Review, 2002)
Diurnal variation in body composition in relation to chronobiological parameters was analyzed in 27 healthy students (22-29 years) four times over one day from 5:35 to 0:15 h. Body composition was determined by multifrequency bioimpedance analysis at fixed frequencies (1, 5, 50, 100 kHz). Resistance (R) and reactance (Xc) were measured. Total, extra and intracellular body water (TBW, ECW, ICW), lean body mass (LBM), and fat mass (FM) were derived, and blood pressure and body temperature were measured. Friedman's ANOVA with post hoc Wilcoxon matched pairs tests revealed a diurnal variability. R and Xc declined in the course of the day. Weight, TBW, ECW, ICW, LBM and ECM increased, whereas height decreased. Chronobiology did not significantly influence FM. Body composition variables displayed inverse associations to RRdiastolic. The diurnal decrease is probably influenced by food and fluid intake. the representative values for body composition should be the morning measures.